First isolation and pathogenicity analysis of a genogroup U strain of infectious hematopoietic necrosis virus from rainbow trout in China. Issue 2 (29th January 2021) - Huo, Caiyun; Ma, Zhihong; Li, Fangbing; Xu, Fuzhou; Li, Tieliang; Zhang, Yue; Jiang, Na; Xing, Wei; Xu, Guanling; Luo, Lin; Sun, Huiling
Abstract: Infectious hematopoietic necrosis virus (IHNV) is a major fish viral pathogen causing acute clinical disease and death in a variety of salmonids. IHNV isolates have been classified into five major genogroups according to the phylogenetic analysis of partial G gene fragments or the complete G gene sequence: U, M, E, L and J. Genogroup U strains have been reported in North America and Japan prior to 1982, and genogroup J is the only genogroup that has been reported in China. Here, one of IHNV strain (BjLL) was isolated from a local farm in China and were characterized in this study. The homogenate tissues of infected fry induced IHNV‐positive cytopathic effects in epithelioma papulosum cyprinid (EPC) cells that were confirmed by RT‐PCR and sequencing. The complete genome sequence of BjLL comprised 11, 129 nucleotides, which had been submitted to GenBank (accession no. MF509592). By the sequence comparison and phylogenetic analysis for the G gene sequence of BjLL with 51 reference sequences in GenBank, we confirmed that this Chinese isolate belonged to genogroup U. Furthermore, virus exposure experiments with juvenile rainbow trout were conducted to assess the virulence and pathogenicity of BjLL. Compared with GS‐2014 of genogroup J, BjLL was an obviously less virulent strain that could result in lower mortality. Besides, typical clinical symptoms and pathological damages could be seen in fish following infection of BjLL. The present study is the first report of genogroup U IHNV infection in China and will provide essential information for future studies on pathogenesis of IHNV BjLL and development of efficient control strategies.